UJI AKTIVITAS ANTIJAMUR HAIR TONIC EKSTRAK JAMUR KUPING HITAM (Auricularia polytricha) TERHADAP PERTUMBUHAN Malassezia furfur - Evanjeli, Nabila Dwi; Budiarti, Retni Sulistiyoning; Aswan, Dara Mutiara; Harlis, Harlis; Mataniari, Raissa; Putri, Husmayani Muny (Biospecies, 2026)
Indonesia has a wealth of biodiversity in the form of various types of fungi, one of which is the black ear fungus (Auricularia polytricha) which is known to contain chemical compounds with the potential to inhibit the growth of pathogenic fungi. This study aims to determine the effect of black ear fungus extract hair tonic on the growth of Malassezia furfur and the best concentration in inhibiting the growth of M. furfur. This type of research is a quantitative study with an experimental method with a Completely Randomized Design (CRD) consisting of 6 treatments, namely: P0: hair tonic brand X, P1: hair tonic without extract, P2: hair tonic extract black ear fungus with a concentration of 10%, P3: 30%, P4: 50%, and P5: 70% with 4 repetitions. The parameters observed were the diameter of the inhibition zone indicating antifungal activity with the best concentration, as well as the hair tonic evaluation test (organoleptic test, pH test, viscosity test, and irritation test). The data obtained were analyzed using ANOVA and continued with the DNMRT test with a confidence level of 95%. The results showed that black ear fungus extract hair tonic had an effect on the growth of M. furfur. The results of the DNMRT test showed that P0 was significantly different from other treatments. Treatment P1 was also significantly different from other treatments. Hair tonic extract concentrations of 10% (P2), 30% (P3), and 50% (P4) were not significantly different. Hair tonic with the highest concentration of 70% (P5) was significantly different from other treatments and had a very strong antifungal category. The conclusion of this study is that there is antifungal activity of black ear fungus extract hair tonic on the growth of M. furfur, and the best concentration of antifungal hair tonic is 70%.